Implementation Theory of Planned Behavior on the Purchase Decision Online and Offline - Kurniawati, Meilinda; Cornelius, Maria Adeline; Ramadhan, Kurniawan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Many things influence consumer purchasing decisions, both internal and external factors, especially with the shift in several purchasing methods in the digitalization era. Theory of planned behavior analyzing important components that have a direct impact on consumer decisions, namely attitude, subjective norms, and perceived behavioral control. Through this literature, usage will be explained theory of planned behavior on purchase offline and online, as well as its development through analysis of several academic journals. Use Systematic Literature Review (SLR) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this research synthesizes scientific evidence and answers the objectives of the research. The time period chosen for this international standard journal is 2019-2022. Found 47 eligible journals according to the selected keywords. Next, process screening with theories and concepts carried out, so that the detailed analysis reviewed focuses on the 30 selected academic journals. The research results stated that the components Perceived Behavior Control on Theory of Planned Behavior, has the most influence on purchasing decisions. Apart from that, socio-demographic characteristics can also be added as supporting variables that can influence consumer purchasing behavior.